Simulation and analysis of triangular structure metamaterial properties at microwave frequencies for medical sensor applications - Riska Amalia; Defrianto Defrianto; Yan Soerbakti; Vepy Asyana; Hewa Yaseen Abdullah (Science, Technology, and Communication Journal, 2024)
The development of antenna technology is increasingly developing in medical sensor applications. The medical sensor antenna can be strengthened with a split ring resonator (SRR) metamaterial structure. Metamaterial is an artificial material that has high resonance manufacturing properties and this can potentially be implemented into microstrip antenna structures. This research aims to design, simulate and analyze the characteristics of metamaterials regarding the frequency function and performance of an antenna combination of 1 – 4 metamaterials with a triangular SRR ring radius of 3.5 mm. The results of this research show that the metamaterial characteristics of permittivity, permeability and refractive index are negative. Furthermore, in the antenna application, the implementation of a 4 SRR triangular metamaterial combination structure has more optimal performance. The results show that antenna performance parameters produce return loss is -41.18 dB, the bandwidth is 3.86 GHz and gain is 3.82 dBi with an omnidirectional radiation pattern.